FDA Approved Drug Library Screening Identifies Robenidine as a Repositionable Antifungal - Mei, Yikun; Jiang, Tong; Zou, Yun; Wang, Yuanyuan; Zhou, Jia; Li, Jinyang; Liu, Lin; Tan, Jingcong; Wei, Luqi; Li, Jingquan; Dai, Huanqin; Peng, Yibing; et al. (Frontiers in Microbiology, 2020)
New antifungal therapies have been imperative, largely due to the increasing burden of fungal infections worldwide, limited arsenal of available antifungal compounds, and the emergence of drug resistance among a variety of pathogenic fungi. In this study, we screened a library of 1068 FDA-approved drugs to identify hits that exhibit broad-spectrum antifungal activity. Robenidine, an anticoccidial agent which has been widely used to treat coccidian infections of poultry and rabbits, was identified in the screening. Physiological concentrations of robenidine were able to significantly inhibit yeast cell growth, filamentation and biofilm formation of Candida albicans, the most extensively studied human fungal pathogen associated with infections in immunocompromised patients. Moreover, we observed a broad-spectrum antifungal activity of this compound towards fluconazole resistant clinical isolates of C. albicans and a wide range of clinically relevant fungal pathogens as well. Intriguingly, the robenidine-treated C. albicans cells conferred hypersensitivity to diverse cell wall stressors and analysis of the cell wall structure by transmission electron microscopy (TEM) showed that cell wall was severely damaged by robenidine, both implying that this compound may target the cell wall integrity signaling pathway. Indeed, after robenidine treatment we found a dose dependent increase in the phosphorylation of cell wall integrity marker Mkc1 which was decreased after long exposure. Furthermore, we provided evidence by RNA-seq and qPCR that Rlm1, the downstream transcription factor of Mkc1, may represent a potential target of robenidine. Therefore, our data suggest that robenidine, a FDA approved anti-coccidiosis drug, displays a promising and broadly effective antifungal strategy and represents a potentially repositionable candidate for the treatment of increasing fungal infections.